REALITAS KEHIDUPAN BERAGAMA ISLAM PARA LANSIA (STUDI PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA TERATAI PALEMBANG) - Tanzila Mawaddah; Ermis Suryana; Muhammad Fauzi (PAI RAFAH, 2020)
The reality of the Islamic life of the elderly is influenced by their age factor which decreases both from psychological and biological factors. At this age, the elderly religion should increase by diligently worshiping and preparing provisions for their lives in the hereafter. The purpose of this study was to determine the reality of the Islamic religious life of the elderly and to find out the fostering of the Muslim religious life of the elderly as well as supporting and inhibiting factors in the efforts of fostering the Islamic religious life of the elderly at the Tresna Werdha Teratai Palembang Social Home.This research uses a descriptive qualitative approach. Subjects in this study were elderly who had reached the age of 60 years and over, with a total of 7 elderly subjects. Data collection methods used were observation, interview, and documentation. The analysis technique used is by way of data reduction, data presentation, and data verification.The results of the study concluded that some subjects experienced a decline in health, but the elderly at the Tresna Werdha Teratai Social Institution in Palembang had begun to prepare themselves for the afterlife by following the coaching that had been carried out such as prayer, five times, fasting, reading the Koran and diligently attend the study and religious guidance in the orphanage.